(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The study employs a contrastive analysis approach to examine how metaphor and figurative language shape cultural perceptions and conceptual frameworks. Findings indicate that while universal cognitive mechanisms underlie metaphorical expressions, language-specific socio-cultural factors influence their semantic and pragmatic applications. The research contributes to cross-linguistic and intercultural studies, enhancing our understanding of metaphorization processes in different linguistic traditions.